The Brutal Truth about Police Brutality - Hargrove, Markhel D. (2015)
Police brutality is a very timely issue as a new case has seemed to pop up every couple of weeks or so; however, police brutality is not a recent phenomenon, but for some reason, it is getting a lot of media attention today. This is perhaps due to the pattern that is occurring in these instances: black victims and white cops. In order to prevent police brutality from happening, several steps must be made to improve the way that police officers act and think in certain situations. First, it is important to teach officers how to properly handle the mentally ill. Different people need to be approached in different ways, especially those who are mentally ill or could be considered as such. Officers need to be patient, calm, and rational when encountering those who have a mental illness. Officers need to learn how to follow procedures, more specifically, when conducting raids. There needs to be tighter restrictions when obtaining no-knock warrants and the officers involved must have accurate intel. The body camera is a program that needs to be instilled in all departments across the country not only for the safety of the suspects and civilians but for the officers who wear them as well. Getting to the root of the problem, race needs to be addressed. The racial demographics of a particular department should correspond to the demographics of its city. This can help reduce the number of police brutality cases brought before police departments throughout the nation